2006
DOI: 10.1089/tmj.2006.12.484
|View full text |Cite
|
Sign up to set email alerts
|

A European Survey on the Possibilities and Obstacles of Electronic Prescriptions in Cross-Border Healthcare

Abstract: This study investigated the possibilities and obstacles for cross-border electronic prescriptions within the European internal market. Cross-border electronic prescribing requires interoperability of the systems and use of standardized solutions. We conducted a survey-based case study. A questionnaire on the use of electronic prescriptions was sent by e-mail to the delegates from 14 European Union (EU) member countries and 2 European Economic Area (EEA) countries during spring-summer 2003. A reply was received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…For example, Kaushal et al [15] found that ambulatory practices using e-prescribing experienced a statistically significant decrease in prescription error rates one year after adoption but they found no statistically significant change in error rates in their control group of non-adopters. E-prescriptions are also easy to read and can thus be processed quickly by pharmacists [17] and with fewer dispensing errors that result from illegible handwriting, or unclear abbreviations or dose designations [16]. They can thus provide time savings for physicians when pharmacists no longer need to call them with queries [9] [11].…”
Section: Electronic Prescribingmentioning
confidence: 99%
“…For example, Kaushal et al [15] found that ambulatory practices using e-prescribing experienced a statistically significant decrease in prescription error rates one year after adoption but they found no statistically significant change in error rates in their control group of non-adopters. E-prescriptions are also easy to read and can thus be processed quickly by pharmacists [17] and with fewer dispensing errors that result from illegible handwriting, or unclear abbreviations or dose designations [16]. They can thus provide time savings for physicians when pharmacists no longer need to call them with queries [9] [11].…”
Section: Electronic Prescribingmentioning
confidence: 99%
“…Within this analytical theme, various studies focus on and describe the European Commission's role in bridging the differences between member states (Leosk et al, 2021;Mäkinen et al, 2006;Marcut, 2019). Studies report that this form of coordination has taken place through agenda setting in the e-GOV action plan 2010, the Malmö and Tallinn declarations and in the 2014-2018 strategy on European e-justice (Berce et al, 2011;Schmidt and Krimmer, 2022).…”
Section: Governance Of Cross-border Digital Public Servicesmentioning
confidence: 99%
“…These regulatory frameworks are considered to be critical conditions in the development and implementation of cross-border digital public services (Leosk et al, 2021;Tinholt et al, 2013). A final role for the EU, as reported in the literature, is promoting standardisation (Nalin et al, 2019;Schmidt and Krimmer, 2022;Soe, 2018) and developing the general building blocks for cross-border services to be implemented by member states (Mäkinen et al, 2006;Nalin et al, 2019;Schmidt and Krimmer, 2022;Soe, 2018, Kramer, 2016Leitold, 2019, Velicogna et al, 2020.…”
Section: Governance Of Cross-border Digital Public Servicesmentioning
confidence: 99%
See 2 more Smart Citations